An impact of agronomic practices of sustainable rice-wheat crop intensification on food security, economic adaptability, and environmental mitigation across eastern Indo-Gangetic Plains - Mishra, J.S.; Poonia, S.P.; Kumar, Rakesh; Dubey, Rachana; Kumar, Virender; Mondal, Surajit; Dwivedi, S.K.; Rao, K.K.; Kumar, Rahul; Tamta, Manisha; Verma, Mausam; Saurabh, Kirti; et al. (Elsevier, 2021)
In the eastern Indo-Gangetic Plains (EIGP), conventional rice-wheat system has led to a decline in productivity, input-use efficiency, and profitability. To address these, a four-year field study was conducted to evaluate the performance of tillage and crop establishment (TCE) methods in rice-wheat-greengram rotation. The treatments included: 1) random puddled transplanted rice (RPTR) - conventional-till broadcast wheat (BCW) - zero-till greengram (ZTG); 2) line PTR (LPTR) - conventional-till drill sown wheat (CTW) - ZTG; 3) machine transplanted rice in puddled soil (CTMTR) - zero tillage wheat (ZTW) - ZTG; 4) machine transplanted rice in zero-till wet soil (ZTMTR) - ZTW - ZTG; 5) system of rice intensification (SRI) - system of wheat intensification (SWI) - ZTG; 6) direct-seeded rice (DSR) - ZTW - ZTG; and 7) zero-till DSR - ZTW - ZTG. During the initial two years, conventional rice system (PTR) recorded a 16.2 % higher rice grain yield than DSR system. Whereas in the fourth year, the rice yields under DSR and PTR were comparable. As compared to SRI/SWI, the average wheat yield in ZT system was significantly high, whereas in rice, SRI/SWI system was comparable with CT system. ZTW after non-puddled rice was at par to CTW after PTR. The ZT wheat produced 4.6 % more yield than CT system. DSR production system consumed 6.8 % less water compared to transplanted system. On the system basis, 10.8 % higher net returns were recorded with CA-based system compared to conventional system. The system energy productivity under CA-based production system was 14–36 % higher than PTR-based systems. CA-based system also led to 8–10 % lower global warming potential (GWP) than conventional methods. The current study indicated that as compared to conventional system, a significant gain in productivity, profitability and energy-use efficiency, and reduction in the environmental mitigation are possible with emerging alternative TCE methods. Long-term expansion and further refinement of these technologies in local areas need to be explored for the second green revolution.